2009
DOI: 10.1177/1362361309335721
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and behavioural adjustment in siblings of children with intellectual disability with and without autism

Abstract: Siblings of children with autism may be at greater risk for psychological problems than siblings of children with another disability or of typically developing (TD) children. However, it is difficult to establish whether autism or the presence of intellectual disability (ID) explains the findings in previous research. Mothers rated the emotional and behavioural adjustment of siblings of children with ID with (N = 25) or without (N = 24) autism. Data were also available 18 months later for siblings of children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 38 publications
(71 reference statements)
5
65
1
1
Order By: Relevance
“…That is, ASD siblings scored higher on the emotional problems scale of the CDI-2; scores on the functional problems scale, while higher in siblings of children with ASD, approached, but failed to reach statistical significance. These findings are commensurate with several recent studies, in which depression and other psychological markers such as emotional problems and internalising behaviours were found to be higher in the context of having a brother/sister with ASD (Lobato et al, 2011;Petalas et al, 2009). These findings also resonate with those from a recent meta analysis, in which siblings of children with DD, including ASD, reported higher levels of depressive symptoms compared to a control group (Vermaes et al, 2012).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…That is, ASD siblings scored higher on the emotional problems scale of the CDI-2; scores on the functional problems scale, while higher in siblings of children with ASD, approached, but failed to reach statistical significance. These findings are commensurate with several recent studies, in which depression and other psychological markers such as emotional problems and internalising behaviours were found to be higher in the context of having a brother/sister with ASD (Lobato et al, 2011;Petalas et al, 2009). These findings also resonate with those from a recent meta analysis, in which siblings of children with DD, including ASD, reported higher levels of depressive symptoms compared to a control group (Vermaes et al, 2012).…”
Section: Discussionsupporting
confidence: 80%
“…Relative to normative controls, siblings of children with a DD such as ASD have been found to report higher levels of separation anxiety (Lobato et al, 2011), emotional problems (Petalas, Hastings, Nash, Lloyd, & Dowey, 2009) and internalising behaviours (Fisman, Wolf, Ellison, & Freeman, 2000). Findings from a review paper (Barlow & Ellard, 2006) and recent meta analysis (Vermaes, van Susante, & van Bakel, 2012) also suggested that siblings of children with a DD might be at greater risk for psychological adjustment difficulties, with internalising behaviours and depressive symptoms found to be higher when compared with a control group.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…This is supported by reports that siblings of individuals with intellectual disability without ASD were emotionally and behaviourally better adjusted than those siblings of individuals with intellectual disability and comorbid ASD [29]. This supports the notion that autism contributes to environmental stress that a sibling needs to adapt to, that it produces a unique set of circumstances for the sibling to navigate, and that autism specific studies, in the midst of such mixed results, need to become more prevalent in addition to disability studies.…”
Section: Discussionmentioning
confidence: 53%
“…Some find no such differences in levels of problems [13], and indeed, some studies suggest that siblings of children with autism are better adjusted than comparison groups of children [14]. Second, even when there are suggestions of negative impact on siblings, the numbers of siblings with concerning levels of behavioural and emotional problems are often very small [15]. Thus, negative impact on siblings’ own adjustment is not universal.…”
Section: ‘Outcomes’ For Siblings Of Children With Autism—what Do We Kmentioning
confidence: 99%